Who found it easy to avail nutritional support through direct benefit transfer under national TB elimination programme in Eastern India: an early evidence from Jharkhand - T., Anupama; Priyadarshini, Megha; Narain, Smiti; Ghosh, Pritam; Mitra, Anindya; Prasad, Ranjit; Pathak, Rajeev Ranjan (International Journal Of Community Medicine And Public Health, 2023)
Background: National TB Programme of India launched Nikshay Poshan Yojana (NPY) through Direct Benefit Transfer (DBT) in April 2018, to provide financial support for additional nutritional requirement during TB treatment. This study aims to understand the enabling attributes in availing Nikshay Poshan Yojana (NPY) through Direct Benefit Transfer (DBT) among notified TB patients from the Indian state of Jharkhand for the year 2019. Methods: This is a retrospective cross sectional descriptive study using secondary data obtained from Nikshay web portal for the Indian state of Jharkhand in the year 2019. State level data on TB Notification and NPY DBT scheme is downloaded from the Nikshay portal in excel format and analysed using Excel 2016 version. Odds Ratio and P value are calculated and analysed to prove any statistically significant associations. Results: The study found higher odds (1.08, 95% CI: 1.03, 1.14; P value 0.004) of having patients who belong to 15 to 65 years, female sex (odds ratio 1.05, 95% CI: 1.01, 1.09; P value 0.018), seeking care in public sector (odds ratio 4.05, 95% CI: 3.83, 4.27; P value <0.00001) and with drug sensitive TB (DS TB) (odds ratio 1.39, 95% CI: 1.1, 1.59; P value <0.00001), among those who received at least one instalment of DBT. Conclusions: TB patients belonging to productive age group, female sex, seeking care in public sector and with DS TB have higher odds of receiving NPY among the study population.